Association of sedentary work with colon and rectal cancer: systematic review and meta-analysis. Issue 4 (28th April 2021) - Lee, JaeYong; Lee, Jongin; Ahn, Joonho; Lee, Dong-wook; Kim, Hyoung-Ryoul; Kang, Mo-Yeol
Abstract : Objectives: There has been no research on sedentary behaviour in the occupational domain that occupies a large portion of the daily life. Methods: We conducted a meta-analysis to investigate the association between sedentary work and colorectal cancer. We searched PubMed, Embase and Cochrane databases up to 12 August 2020 for peer-reviewed journal articles that assessed the association between sedentary work and colon or rectal cancer. Pooled estimates of ORs were obtained using random effects models. Statistical tests for publication bias, heterogeneity and sensitivity analysis were applied. Results: Of the 5 381 studies initially identified, 23 studies with 64 reports were eligible for inclusion. Sedentary work significantly increased the risk of colon cancer (pooled OR=1.21, 95% CI 1.11 to 1.31, p value ≤0.0001) and rectal cancer (pooled OR=1.08, 95% CI 1.00 to 1.16, p value=0.0395). The adjustment for leisure time physical activity attenuated the association and made the risk estimates non-significant for sedentary behaviour, but the association was independent of sex, control of body mass index and assessment of sedentary behaviour. Conclusions: We found evidence of association between sedentary work and the risk of colon or rectal cancer. Limiting excessive sedentary work could be an important means of preventing colon and rectal cancer.